(untitled) (Research, Society and Development, 2020)
This article discusses the culture of peace in the context of Brazilian legal education, from the perspective of the 2015 Code of Civil Procedure and Resolution No. 05/2018 of the National Council of Education. It proposes a reflection on the current Brazilian legal education and its correspondence to the culture of litigation, in addition to a discussion related to the role of the teacher for the training of legal operators who understand the need and relevance of the use of alternative means of conflict resolution. For the methodological conduct of the study, a qualitative approach methodology will be used, through the deductive method, with the aid of bibliographic and documentary research. The notes found demonstrate the need for change both in the curriculum of legal courses, so that it is taught to work with conflict and to value consensual means of resolution, as well as in the teaching methodology for the use of one that privileges dialogue, critical reflection, interdisciplinarity and the promotion of the dignity of the human person.